Organiziranost, mediji in stiki Slovencev v Szombathelyu/Sombotelu - Munda Hirnök, Katalin (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2003)
Positive changes in the field of legal protection of minorties in Hungary in the 1990s contributed to political and cultural organizing of Slovenes in the Raba region/Porabje and Budapest. After the passing of the Law on the Rights of National and Ethnic Minorities in Hungary (1993), this organizing took place also in settlements outside the autochthonous territory, above all in larger towns (Szombathely, Mosonmagyarovar, Szekesfehervar). The article brings results of the research study Status of Slovenes in Hungary, outside the territory of their autochthonous settlement (the case of Slovenes in Szombathely), concerning organizing, mass media, mutual contacts. Qualitative analysis of a smaller sample, mainly of members of two Slovene organizations (Slovene minority self-management, Slovene cultural society Avgust Pavel) in Szombathely, shows that common programs of both the organizations, presence of minority media and (formal and informal) contacts with the area of settlement, with Slovenes in other parts of Hungary, as well as with Slovenes in Slovenia, positively contribute to the preservation and promotion of ethniccharacteristics.
Keywords: Hungary; Madžarska; Porabje; narodne manjšine; Hungarian Slovenes; Porabski Slovenci; association; društva; mass media; množični mediji